Analysis of Relations Organic Carbon in Sediment with Growth Rate of Seagrass Enhalus acoroides and Thalassia hemprichii - Nasdwiana, Nasdwiana; Hildayani, Hildayani (Hasanuddin University, 2023)
This study aims to determine and analyze the relationship of organic carbon in sediments with the growth rate of seagrass Enhalus acoroides and Thalassia hemprichii. This research was conducted on Langkai Island, Makassar City, with three points, namely near the coast, in the middle and near the coral reefs. The research phase began with marking the seagrass E. acoroides and T. hemprichii in the field, then measuring the growth rate of the seagrass, followed by a sieving process to determine the texture of the sediment, and burning to determine the organic carbon content of the sediment. The results showed that differences in sediment organic carbon showed a weak correaltion and insignificant. The differences in the growth rates of seagrass E. acoroides and T. hemprichii based on point were not significant. The relationship between organic carbon and sediment texture has a weak correlation and insignificant. Similarly, the effect of organic carbon on the growth rate of seagrass E. acoroides and T. hemprichii also showed a weak correlation and insignificant.